The Study of the students’ Speaking Performance in Demonstrating Product Advertising - Ilinawati Ilinawati (STKIP PGRI Lubuklinggau, 2021)
This Study discusses analyzing the students’ speaking performance in demonstrating the product advertising. There were 24 second-semester students of the English Language Study Program of a private university who participated in this study. The researchers conducted this study by analyzing the students’ speaking scores and categorizing the students’ speaking achievements into five levels of ability. There were five levels of ability that cover the aspects of speaking skills. Those levels are poor, fair, average, good, and excellent. The finding showed that the excellent level contributed as 42 %, then average and good level have the same percentage as 25 % and the two last levels were fair and poor got 4 % for each of them. The average score of students’ speaking performance in demonstrating the product advertising was at a good level. It could be described that the students’ speaking performance was good, both in students cognitive and mental preparation.